i-choose u: Development of Decision Support System Using Skyline Technique (Preference Query Technique): The Case of Choosing Malaysian Higher Learning Institutions - Elhassan, Omer Ibrahim Elkhder (2011)
This study focuses on Malaysian public universities marketing strategies which mainly used to attract international students who have the intention to enroll in higher learning institutions in Malaysia. The main objective of this study is to develop decision support system prototype (DSS) using preferences queries technique (skyline technique), in order to solve the issue of facing challenges that can be consequences of wrong selection of universities or colleges that had been made by students and may influence in their performance. This system aim to help international students to choose suitable college based on their criteria as well as to help them to make the right decision when they want to select one of the public universities in Malaysia. In this research; we used rapid application development (RAD) method. The DSS prototype (i-choose u) in this study constructed by using Java Server Pages (JSP) and MYSQL for database development, which are open sources software. The DSS prototype (i-choose u) suggests maximum five universities to international students that are most suitable to students based on student’s criteria.